Developing Asian Bondmarkets - Ito, Takatoshi (ANU Press, 2014)
The absence of vibrant bondmarkets in East Asia was a significant contributor to the 1997-98 financial crisis. Ever since, the development of local bondmarkets has been a major objective of financial reforms in many East Asian economies. This effort has been frustrated by the inability to reach a consensus on whether Asian bondmarkets are truly needed in East Asia, whether they can be made viable in the competitive environment of the global economy, how they should be created and what role intergovernmental cooperation should play in their definition and creation. Developing Asian Bondmarkets helps build this consensus, proposing how to develop robust and efficient bondmarkets in East Asia. This book, the first of its kind, comes from the Finance Forum of the Pacific Economic Cooperation Council.